Phase angle values, a good indicator of nutritional status, are associated with median value of hemoglobin rather than hemoglobin variability in hemodialysis patients. Issue 1 (1st January 2021) - Kim, Do Hyoung; Oh, Dong-Jin
Abstract: Background: Our aim was to elucidate whether Hb variability affects nutritional status in HD patients. Methods: This study included chronic HD patients ( n  = 76) with available monthly Hb levels up to 24 months prior to the body composition monitoring (BCM) measurement. The parameters obtained in the BCM included body mass index (BMI), lean tissue index (LTI), fat tissue index (FTI), body cell mass index (BCMI), overhydration/extracellular water ratio (OH), and phase angle (PhA). The coefficient of variation (Hb-CV), standard deviation (Hb-SD), and range of Hb (Hb-RAN) were used as indexes of Hb variability. In addition, minimum (Hb-Min), maximum (Hb-Max), average (Hb-Avg), and median (Hb-Med) Hb levels (g/dL) were analyzed. Results: There were no significant differences in clinical, biochemical, and nutritional indexes based on the Hb-CV level. Compared to patients with an Hb-Med ≤ 10.77, those with an Hb-Med >10.77 had higher albumin levels, total iron-binding capacity (TIBC), and PhA and lower average weekly prescribed darbepoetin. Age, female sex, OH, and darbepoetin dosage were negatively correlated with PhA. Serum albumin, phosphorus, TIBC, Hb-Med, and Hb-Avg were positively correlated with PhA. In multiple linear regression analysis, PhA was positively associated with Hb-Med and serum albumin level, whereas PhA was negatively associated with age and female sex. The area under the curve (AUC) of Hb-Med was 0.665 ( p  = 0.040) in predicting PhA >5.00° Conclusions: PhA was not affected by indexes of Hb variability, whereas PhA was associated with Hb-Med in chronic HD patients.